2021
DOI: 10.1002/er.7371
|View full text |Cite
|
Sign up to set email alerts
|

Materials development and prospective for protonic ceramic fuel cells

Abstract: Protonic ceramic fuel cells (PCFCs) are considered a potential and more efficient upgrade to conventional solid oxide fuel cells (SOFCs). This is predominantly due to their capacity to operate efficiently at low and intermediate temperatures and their quality of nonfuel dilution at the anode during operation. This review presents a detailed exposition of the material development strategies for the major components of PCFCs (i.e., electrolyte, cathode, and anode) and how they differ from the traditional SOFCs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 226 publications
(248 reference statements)
1
23
0
Order By: Relevance
“…This makes the task of creating high-efficiency solid oxide devices for electrochemical applications very important for now. The oxygen-and proton-conducting solid oxides may be components of various devices including fuel cells and electrolyzers [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Most well-known electrolytes for medium-temperature solid oxide fuel cells (500-700 • C) are characterized by the perovskite or perovskite-related structure ABO 3−δ [22].…”
Section: Introductionmentioning
confidence: 99%
“…This makes the task of creating high-efficiency solid oxide devices for electrochemical applications very important for now. The oxygen-and proton-conducting solid oxides may be components of various devices including fuel cells and electrolyzers [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Most well-known electrolytes for medium-temperature solid oxide fuel cells (500-700 • C) are characterized by the perovskite or perovskite-related structure ABO 3−δ [22].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the presence in the B-sublattice the metal with constant oxidation state such as indium, the chemical properties become completely different despite the same +8/+6 sum of cationic charges. As it was shown recently [ 17 ], the composition BaLa 2 In 2 O 7 demonstrates nearly pure protonic transport under wet air and low temperatures and this phase can be potentially considered as the electrolytic material for the solid oxide fuel cell; therefore, the development of new materials with improvement properties is very relevant today [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because proton‐conducting electrolytes are quite different from oxygen ion conducting electrolyte fuel cells in the choice of materials, fuel cells using proton‐conducting electrolytes are usually called protonic ceramic fuel cells (PCFCs). With the development and application of high‐performance materials, PCFCs have been well developed in the past 10 years, and their performance has also been greatly improved 17–20 …”
Section: Introductionmentioning
confidence: 99%
“…With the development and application of high-performance materials, PCFCs have been well developed in the past 10 years, and their performance has also been greatly improved. [17][18][19][20] Studies have shown that the main factor limiting the output performance of PCFCs at medium to low temperatures (400-600 C) is the sluggish ORR process of the cathode material. To improve the overall output performance of fuel cells, a large number of oxides are used as cathode materials.…”
Section: Introductionmentioning
confidence: 99%